(untitled) (Journal of Engineering, 2023)
ole in all sta Oil well logging, also known as wireline logging, is a method of collecting data from the well environment to determine subterranean physical properties and reservoir parameters. Measurements are collected against depth along the well’s length, and many types of wire cabling tools depend on the physical property of interest. Well probes generally has a dynamic respon to changes in rock layers and fluid composition. These probes or well logs are legal documents that record the history of a well during the drilling stages until its completion. Well probes record the physical properties of the well, which must then be interpreted in petrographic terms to obtain the characteristics of the rocks and fluids associated with the well. Many bases on which well probes are depend on obtaining information, and preventing the rocks from responding to stimuli sent by special devices, whether those stimuli are electrical, radioactive, or acoustic. In addition, there are electrically controlled mechanical bases used to measure the diameter of the well, its flow, pressure, perforation, and taking samples. Wireline refers to the technique of using the cable to deliver special equipment to the bottom of the well to repair, evaluation, or equipment recovery. A simple wireline consists of a shiny metal wire (called a slickline) that is very durable for tensile and wear operations. It is of (0.108" or 0.125") diameter. The equipment is installed at the end of the wire. Still, sometimes a braided cable is used from many small steel wires (Braided line), which makes it stronger and heavier than the first type. The information obtained from the logs is considered to assess geological areas based on porosity, permeability, hydrocarbon fluids, and shale ratio. Well logging uses logs that are much cheaper than core operations and also cheaper than the information obtained from drilling mud. This review aims to pinpoint on the most important logging processes used in oil wells, as well logs have an effective role in all stages of the oil industry.